Muscular and Physical Response to an Agility and Repeated Sprint Tests According to the Level of Competition in Futsal Players - García-Unanue, Jorge; Felipe, José Luis; Bishop, David; Colino, Enrique; Ubago-Guisado, Esther; López-Fernández, Jorge; Hernando, Enrique; Gallardo, Leonor; Sánchez-Sánchez, Javier (Frontiers in Psychology, 2020)
The aim of this study was to evaluate the neuromuscular response to an agility and repeated sprint ability test according to the level of competition in futsal players. A total of 33 players from two elite teams and one amateur team participated in the study. The participants completed an agility T-Test, a 30 m-speed test, and a Repeated Sprint Ability (RSA) test. A countermovement jump test and a tensiomyography test of the rectus femoris (RF) and biceps femoris (BF) of both legs were carried out before and after the tests. RSA test revealed better sprint times in elite players compared to amateurs in the 7 bouts, as well as in the 30m sprint and in the agility test (p<0.05). Before the tests, elite players showed higher sustain time (Ts) in RF (+31.03 ms; ES: 0.76) and BF (+28.73 ms; ES: 0.73), higher half-relaxation time (Tr) in BF (+20.79 ms; ES: 0.94), and lower delay time (Td) in BF (-2 ms; ES: 1.19) compared to amateur players. However, post-test values did not present any significant differences (p>0.05). In conclusion, elite players showed greater performance in the RSA test, in the 30 m tests and in the agility test compared to amateur players. The contractile properties were not a key factor in the RSA performance of the futsal players.